Optimization of Digital Subtraction Angiography Parameters for Radiation Safety: A Systematic Review of Current Evidence - Abdullah M Al Shahrani; Raddad Mohammed Almubashir; Eilaff Ali Albowaidi; Shereen Abdullah Albehairi; Abdulaziz Saad Aldaubi; Faisal Mohammed Al Sonbul (Utilitas Mathematica, 2025)
Background Digital Subtraction Angiography (DSA) is a fundamental modality of radiology, but the optimization of radiation exposure while preserving diagnostic image quality remains a challenge. Systematic review This review summarizes the previous findings of recent studies regarding radiation safety improvements in DSA utilization, guided by new technologies, procedures, and algorithms. Material and Methods Relevant publications during the period 2000-2025 were included with emphasis on dose-reduction approaches, standardization of protocols, and novel imaging technologies; specifically digital variance angiography (DVA) and artificial intelligence (AI)-assisted angiography [9-12,21,23]. Performance indicators included dose measurements for patients, image quality, and occupational radiation exposure. Results Recent developments, for example the low-rate fluoroscopy [7,8], enhanced filtration and focal spot size [6], and advanced image-processing algorithm [16,32], can achieve considerable radiation reductions while not affecting image quality. DVA has been shown to reduce dose up to 70 % and to still be diagnostic effective [10,11]. Additional safety and accuracy were achieved via AI-powered angiographic reconstruction [14,21] and low-dose 3D rotational angiography. Following the established radiation management guidelines is still key to clinical implementation [1,2,5,40]. Conclusion The provision of integrated technological and procedural approaches to optimization of DSA parameters will greatly lower radiation exposure for both patients and staff. Future research should investigate standardization and multicenter validation as well as AI-based innovation to develop repeatable and globally applicable radiation-safety protocol for interventional imaging